NUMERICAL STUDY OF THE EFFECT OF WALL THICKNESS AND INTERNAL PRESSURE ON VON MISES STRESS AND SAFETY FACTOR OF THIN-WALLED CYLINDER FOR ROCKET MOTOR CASE - Wibawa, Lasinta Ari Nendra (Universitas Pendidikan Ganesha, 2020)
The rocket motor is an important part of rockets. The rocket motor works using the pressure vessel principle because it works in an environment with high pressure and temperature. This paper investigates the von Mises stress that occurs in thin-walled cylinders and safety factors for rocket motor cases due to the influence of the wall thickness and internal pressure. Dimensions of the cylinder length are 500 mm, outer diameter is 200 mm, and cap thickness is 30 mm. The wall thickness is varied 6, 7, 8, and 9 mm, while the internal pressure is varied 8, 9, and 10 MPa. Stress analysis is performed using the finite element method with Ansys Workbench 2019 R3 software. The simulation results show that the maximum von Mises stress decreases with increasing wall thickness. The maximum von Mises stress increases with increasing internal pressure. The material has a safety factor higher than 1.25 for all variations in wall thickness and internal pressure. It means that the material can withstand static loads. The verification process is done by comparing the results of finite element analysis with analytical calculations for maximum hoop stress and maximum axial stress with a fixed boundary condition. The results of maximum hoop stress and maximum axial stress using finite element analysis and analytical calculations are not significantly different. The percentage of errors between analytical calculations and finite element analysis is less than 6 percent.